The Sacred Nature of White Stone in the Temple Construction of Andrey Bogolyubsky - Alexandr I. Skvortsov (Publishing house "Sreda", 2021)
The article deals with the issues of the sudden appearance of white-stone construction in the middle of the XII century in the North-East of Russia, in the Vladimir Principality, which are practically not affected by science. The purpose of the study is to identify the most likely sources that influenced the process of origin and formation of the unique style of Vladimir-Suzdal architecture during the reign of Andrei Bogolyubsky (1157-1177). The research methods were reduced not only to the analysis of the Old Testament texts, with which the Great Vladimir Prince was well acquainted and admired their heroes during the construction of his white-stone churches, but also to the identification of the peculiarity of the current situation, individual facts of the prince's activity and the nature of his character, which became an active incentive to the introduction of white stone instead of bricks, which took a sacred character for Andrey Bogolyubsky. The result of the study is as follows: first, the symbolism of the white color, drawn from the biblical testaments of the consubstantial God, became the leitmotif for the architectural creations of the Vladimir prince; second, the perceived Old Testament building traditions stimulated the growth of original forms of Vladimir-Suzdal white stone architecture, which have no close analogies in the entire area of neighboring countries. In the light of the current inclusion of white stone buildings in the UNESCO World Cultural Heritage, the aspect of their study not only brings scientific novelty to the already established interpretation, but also entails a rethinking of the practical orientation of restoration and restoration work on them.